Catastrophic drainage from the northwestern outlet of glacial Lake Agassiz during the Younger Dryas - Norris, S. L.; Garcia-Castellanos, D.; Jansen, J. D.; Carling, P. A.; Margold, M.; Woywitka, Robin; Froese, D. G. (My University, 2021)
Catastrophic meltwater drainage from glacial Lake Agassiz has been hypothesised as a trigger for large-scale ocean circulation change initiating the Younger Dryas cold reversal. Here we quantify the flood discharge that formed the northwestern outlet of Lake Agassiz using a one-dimensional step-backwater model and a zero-dimension gradual-incision model. Applying these two independent models, we estimate a peak discharge range of 1.8-2.5 × 106 m3 s-1 and a flood volume of ~21,000 km. Such a discharge can only be derived from Lake Agassiz rather than one of the two smaller regional glacial lakes: Churchill or Meadow. When coupled with existing ice margin chronologies, these results demonstrate that the northwestern outlet of Lake Agassiz provides a viable link for catastrophic meltwater to drain to the Arctic Ocean over a 5-10 month period during the Younger Dryas, though it is unclear whether this was near its beginning.
Keywords: Lake Agassiz; Younger Dryas; meltwater drainage